MODELING A PROCESS FOR THE REMOVAL OF CADMIUM FROM SIMULATED WASTEWATERS BY ELECTRODEPOSITION ON STAINLESS STEEEL TUBES BUNDLE (Journal of Engineering, 2011)
Electrochemical processes can provide valuable contributions to the protection of the environment through implementation of effluent treatment and production-integrated processes for theminimization of waste and toxic compounds. The performance of a novel pilot scale, batch re-cycled, flow-through cell, with stainless steel tubes bundle cathode in the removal of cadmium was investigated utilizing the potential results obtained from a batch mode. The studied electrochemical reaction was the cathodic reduction of Cd+2 using 0.5 M sodium sulphate as supporting electrolyte. The analyzed parameters were different initial Cd+2 concentrations (50,100, 200, 300, 400 ppm) and different electrolyte flow-rates (100, 200, 250, 300, 350 L/hr), the tubes number was 920 of 0.6 cm diameters.The overall empirical mass transfer correlation was found to be: Sh = 0.051 Re 0.859 Sc1/3For 5 < Re < 20 and Sc = 649 Experimental results, analysis and correlations showed good performance of the cell and proved its adequacy in the removal of Cd+2 from simulated effluents.